Unveiling the role of frugal and digital capabilities in the financing of deep tech startups - Keully Cristynne Aquino Diógenes; Ana Carolina Calçado Lopes Martins; Claudia Pavani; Felipe Mendes Borini; Guilherme Ary Plonski (Regepe Entrepreneurship and Small Business Journal)
Objective: Showcasing the Role of Digital Technologies, Frugal Innovation, and Imitability Attributes in Attracting Investments in Deep Tech Startups in an Emerging Economy. Methodology/approach: The primary data for this research were obtained from a sample of 216 deep tech startups from various sectors, located in São Paulo. The hypotheses were tested using structural equation modeling through the Partial Least Squares (PLS-SEM) method. Main results: Private investors are attracted to digital technologies and the attribute of being difficult to imitate. However, although there is a positive association between the capacity for frugal innovation and the hard-to-imitate attribute, no indirect effects of this capacity on investments were identified. Theoretical/methodological contributions: Focusing on emerging economies, this study contributes to the literature that investigates which factors explain investments in deep tech startups. Moreover, it contributes to the literature linking frugal innovation and technological complexity. Relevance/originality: Deep tech startups require substantial financial resources; however, in emerging markets, there is a scarcity of investment resources. Based on the RBV (Resource-Based View), this research demonstrates which capabilities are able to arouse the interest of private investors in the context of emerging economies. Social/management contributions: For entrepreneurs, the research highlights the importance of digital technologies in attracting investments. For investors and public policy makers, the study emphasizes the association of the capacity for frugal innovation with the attribute of imitability in deep tech startups.